Designing BatikFractal Using Adobe Photoshop - Ariesto Hadi (CV TOPAZART, 2022)
Tourism is an important economic sector of Indonesia, for it is one of the significant devisa sources for Indonesia. To increase the role of sustainable tourism in economic growth, promoting tourism is essential to attract tourists continuously and effectively. Nowadays, promotion uses many methods and media, including mobile devices, for the fast-growing smartphone users globally. Therefore, mobile multimedia is considered an effective medium to convey promotion messages for tourism, as the essential to promote Indonesia tourism. According to Luther, this research consists of six phases of the Multimedia Development Life Cycle, such as concept, design, obtaining content material, assembly, testing, and distribution. During the assembly phase, the mobile multimedia is built using Adobe Photoshop. The application is expected to increase batik design innovation who visit Indonesia.